Assessing marginal wetland loss to agricultural expansions in the Lower Ogun River Basin of Southwest, Nigeria - Adeleke, Benjamin Oluwafemi; Orimoogunje, Oluwagbenga O.I; Ekanade, Olusegun (Journal of Wetlands Ecology, 2020)
Wetlands are significant to the environment and economic survival of people most especially in the rural areas of the tropical world; their sustainability is however threatened by agricultural drainages and demographic pressure. The detrimental influence of agricultural expansion on wetland loss was examined using both primary and secondary data. The primary data was collected through questionnaires administration and interviewing of hundred members of Fadama Users Group (FUG) (i.e. 10%). The secondary data included satellite images of 1972, 1984, 2000 and 2015 analyzed using GIS technique and corresponding census data by simple descriptive percentage method. The results revealed that marginal wetlands lost about; 3180.60 ha between 1972 and 1984, 1936.08 ha between 1984 and 2000 and 805.32 ha between 2000 and 2015, to farmlands intensification throughout the periods of study. Wetlands ecosystem was also expected to lose more ground as the population growth is unabated and, more so, with the projected farmlands growth of about 4730.04 ha i.e. about 36.36% in 2030; there is, therefore tendency for serious depletion of marginal wetlands in the future.